2005
DOI: 10.1088/0022-3727/38/10a/043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the crystal-surface unevenness on the angular spread of an x-ray diffracted beam

Abstract: One of the factors influencing the focus size in diffractive–refractive optics is the quality of diffracting surface. If the surface is uneven, as it is when the silicon crystal surface is only etched, then the diffraction at each point of the surface is a combination of an asymmetric and inclined diffraction (general asymmetric diffraction). This somewhat deviates and spreads the diffracted beam. The integration over the surface hit by an incident beam gives the angular spread of the diffracted beam. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…At ϕ′ = 0 and 180°, h -GaN­(000 m ) ( m = 2, 4, 6) is also observable. It has been reported that the surface roughness can affect the fwhm of a peak in a low-angle incident X-ray beam to the surface . In Figure b, the surface is relatively rough at the sub-micrometer scale.…”
Section: Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…At ϕ′ = 0 and 180°, h -GaN­(000 m ) ( m = 2, 4, 6) is also observable. It has been reported that the surface roughness can affect the fwhm of a peak in a low-angle incident X-ray beam to the surface . In Figure b, the surface is relatively rough at the sub-micrometer scale.…”
Section: Results and Discussionmentioning
confidence: 87%
“…It has been reported that the surface roughness can affect the fwhm of a peak in a low-angle incident X-ray beam to the surface. 21 In Figure 1b, the surface is relatively rough at the sub-micrometer scale. For the accuracy in fwhm, as seen in Figure 4, n = 3 for c-GaN and m = 6 for h-GaN were chosen.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…We used two Si(111) crystals in an asymmetric arrangement, with an asymmetry angle of = 15 ; with a beam energy of 7.31 keV, then  B = 15.7 . The impinging radiation formed an incident angle of 0.7 with the surface which meant that this arrangement is surface-sensitive (Hrdá et al, 2003(Hrdá et al, , 2005. The cut-off edge (creating an L-shape crystal) of the crystal (Fig.…”
Section: Description Of Device and Experimental Arrangementmentioning
confidence: 99%
“…Consequently, the position of the diffraction events on the optical path also somewhat depends on x. As the sagittal deviation δ after diffraction from the wall of the groove is [2] |δ| = |K dy/dx|, (9) which is of the order of 10 −4 rad or less, these displacements are of the order of 10 −2 -10 −3 mm or less for dy/dx < 1 and this effect on the focus size may be obviously neglected. Only for a very steep wall of the groove might this play a role.…”
Section: Calculation Of the Focus Broadeningmentioning
confidence: 99%
“…As in any focusing device, there is a need to determine the minimal focus size achievable by the method. The quality of the diffracting surface may play a significant role when highly asymmetric diffraction is used; this influence is discussed elsewhere [8,9] . Apart from the focus distortion caused by the crystal surface quality, we will try to discuss the theoretical aberration which limits the achievable focus size in this method.…”
Section: Introductionmentioning
confidence: 99%